Estruturas de covariância de peso em função da idade de animais nelore das regiões sudeste e centro-oeste - Bruno Dourado Valente (2007)
Body weight records from 90 to 450 days of age of Nellore animals from the Southeast and Center West regions were used do estimate covariance structures of age dependent random effects for each region using random regression models. Covariance components of the regression coefficients were estimated by EMREML using the software REML90. The fixed effects of contemporary groups and direct additive genetic, maternal additive genetic and permanent environment random effects were modeled by quadratic Legendre polynomials. The comparisons included structures of covariance and correlation of random effects, direct and maternal heritabitability, direct and maternal correlations and the ratio between genetic variances from different regions. The heritability, covariance and correlation structures showed similar patterns for both regions. The residual variance and the permanent environment were smaller for Center West region as well as the maternal additive genetic from 150 to 400 days of age. The estimated body weight direct heritabilities were slightly greater for animals from Center West than of those from Southeast region in all evaluated age interval. Fixed effect trajectories in function of age of different contemporary groups showed different patterns, suggesting the necessity of specific set of regression coefficients for each contemporary group. The maternal additive genetic variance showed greater heterogeneity between regions than the direct additive genetic variance.